Surgical and conservative management of symptomatic leiomyomas during pregnancy: a retrospective pilot study = Operatives und konservatives Therapiemanagement von symptomatischen Leiomyomen in der Schwangerschaft : eine retrospektive Pilotstudie - Rothmund, Ralf; Taran, F. A.; Boeer, B.; Wallwiener, Markus; Abele, H.; Campo, R.; Wallwiener, D.; Brucker, S.; Rall, K. (Geburtshilfe und Frauenheilkunde, 2013)
Purpose: Evidence regarding distinguishing characteristics of women with symptomatic leiomyomas during pregnancy who undergo myomectomy during pregnancy and those who respond to conservative treatment is sparse because it mostly derives from case reports and small patient series. As the first of its type, the present study analyzed the characteristics of women with symptomatic leiomyomas treated with myomectomy during pregnancy and those treated conservatively. Methods: We performed a computer search of medical records from 1 January 2001 to 31 March 2011 using the International Classification of Diseases Codes for pregnancy, myomectomy and leiomyomas during pregnancy. Results: 27 patients were admitted during pregnancy directly related to leiomyomas; 17 of the 27 patients received conservative treatment for symptomatic leiomyomas, and 10 patients had surgery during pregnancy: 3 had undergone diagnostic surgical procedures and 7 myomectomy. Perioperative and postoperative morbidity was low in all women in our sample. Conclusion: In our pilot study, myomectomy during pregnancy was safely performed in carefully selected patients, with subserosal or pedunculated leiomyomas that failed to respond to conservative treatment, with low perioperative and postoperative morbidity.